Holistic Marketing in the System of Business Interactions of the Enterprise - Eshmamatovich, Xajikulov Bektash (European Journal of Life Safety and Stability (2660-9630), 2021)
The article deals with the application of the concept of holistic marketing as the basis for integrated interactions between a firm and a client. The main parameters of the system of the marketing paradigm under study are analyzed in conjunction with the determination of the value of each participant. The author’s interpretation of the evolutionary stages of the development of interactions between partners in market contacts is given.